Synthesizing the Machine's Availability in Overall Equipment Effectiveness (OEE) / Normariah Che Maideen ...[et al.] - Che Maideen, Normariah; Budin, Salina; Sahudin, Shuib; Ab. Samat, Hasnida (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Overall Equipment Effectiveness (OEE) is an important and reliable method that could be adopted in manufacturing environment. This method is significant to evaluate machines performance and later setting up goals for the industry to keep improving their performance. Previously, numerous researchers have been conducted to adopt these tools and find the OEE value for specific industry. As a bottom-up approach, the method proposed is to implement into the system. However, study on the opposite way which is a top-bottom approach is still unavailable. From the OEE calculation that measure machine's availability, performance and quality, there is no specific study to re-evaluate the value gathered. Thus, this paper proposed a top-down framework to evaluate current performance of the machine. The outcome from the framework can then be used in producing simplified Machinery Failure Mode Effect Analysis (MFMEA). A case study in a manufacturing company has been adopted to demonstrate the implementation of the proposed framework.